Hubungan Kecanduan Gadget dengan Interaksi Sosial Siswa - Yenita Putri Widyaningrum; Yovitha Yuliejantiningsih; Agus Setiawan (Journal on Education, 2024)
The increasing development of technology can have both positive and negative impacts. One of the negative impacts caused by technological development is gadget addiction. Facts state that most teenagers today are addicted to gadgets. As a result, students spend a lot of time playing gadgets, reducing students' interaction with the environment and social. This study aims to determine the relationship between gadget addiction and social interaction in class X PPLG students of SMKN 11 Semarang. The population in this study were students of class X PPLG SMK Negeri 11 Semarang which consisted of 4 classes and totaled 144 students. Of these, 106 students were used as research samples. The research data was collected using a questionnaire distributed online and analyzed by regression analysis method using SPSS version 26. Based on the results of the analysis, it has been obtained sig value (2-tailed) on the correlation test of 0.000 <0.05 . Thus, it can be concluded that there is a significant relationship between gadget addiction and social interaction in students.